EFEKITIVITAS PELAYANAN PADA KANTOR KEPALA KAMPUNG PEPAS EHENG KABUPATEN KUTAI BARAT - Salju, Irawati (PREDIKSI, 2016)
EFFECTIVENESS OF SERVICE ON HEAD OFFICE KAMPUNG PEPAS EHENG DISTRICT KUTAI BARAT Service is the main task of the essence of the figure of the apparatus, as a servant of the state and public servants. This task has been clearly outlined in the preamble of the fourth paragraph of the 1945 Constitution, which covers 4 (four) aspects of the basic service of the apparatus to the people, namely to protect the whole Indonesian nation and the entire Indonesian blood sphere, to promote the general welfare, to educate the nation and to implement the world order based on independence , eternal peace and social justice are further clarified in the Decree of the Minister of Administrative Reform. 63 of 2003 which outlines the general guidelines of public service delivery.Performance of the Village Government of Pepas Eeheng , West Kutai District saw the p roductivity of Village Government in conducting the service. D i Village pepas Eeheng village government really see in terms of needs not wants, use and benefit for society is good enough. For field activities the village government demands the optimization of time to work for the project worker so that the activities can be completed exactly within the time specified in the employment contract. if there are activities that can be done with self-help, the village government invites the community to work together to complete infrastructure development. The productivity of the Village Government in completing the Infrastructure Development in Pepas Eeheng Village is necessary to further increase its Productivity Productivity in terms of completing infrastructure development, in initiating activities not necessarily dependent on complete new materials to be able to start, and for support from the village government itself in the field to run with both as well as the utilization of working time to the maximum.Proof performance Village Government prioritize services to meet the needs and aspirations of the people in the village ng yes. Responsiveness and spirits will be followed up in the village musrembang to be proposed in the village development program not necessarily all aspirations can enter into the infrastructure development program because the aspirations will be assessed in terms of the needs of the community not from the desire which then becomes the development priority in the village.Service to the public is the main thing, from 310 total of the existing letter then the researcher conclude that service of head office of the village has reached and can be felt directly by society. Nevertheless, it is necessary to improve service to the public in order to maximize the role of good public services.=====================EFEKITIVITAS PELAYANAN PADA KANTOR KEPALA KAMPUNG PEPAS EHENG KABUPATEN KUTAI BARAT Pelayanan merupakan tugas utama yang hakiki dari sosok aparatur, sebagai abdi negara dan abdi masyarakat. Tugas ini telah jelas digariskan dalam pembukaan UUD 1945 alinea keempat, yang meliputi 4 (empat) aspek pelayanan pokok aparatur terhadap masyarakat, yaitu melindungi segenap bangsa Indonesia dan seluruh tumpah darah Indonesia, memajukan kesejahteraan umum, mencerdaskan kehidupan bangsa dan melaksanakan ketertiban dunia yang berdasarkan kemerdekaan, perdamaian abadi dan keadilan sosial selain itu diperjelas lagi dalam Keputusan Menteri Pendayagunaan Aparatur Negara No. 63 tahun 2003 yang menguraikan pedoman umum penyelenggaraan pelayanan publik.Kinerja Pemerintah Desa Pepas Eeheng, Kabupaten Kutai Barat terlihat adanya produktivitas Pemerintah Desa dalam menyelesaikan pelayanan. Di Desa Pepas Eeheng pemerintah desa betul-betul melihat dari segi kebutuhan bukan keinginan, penggunaan dan manfaat bagi masyarakat sudah cukup baik. Untuk kegiatan lapangan pemerintah desa menuntut optimalisasi waktu untuk bekerja kepada pekerja proyek agar kegiatan bisa selesai tepat dengan waktu yang ditentukan dalam kontrak kerja. jika ada kegiatan yang bisa dikerjakan dengan swadaya maka pemerintah desa mengajak masyarakat untuk bekerja sama menyelesaikan pembangunan infrastruktur. Produktivitas Pemerintah Desa dalam menyelesaikan Pembangunan Infrastruktur di Desa Pepas Eeheng yaitu perlu lebih meningkatkan lagi Produktivitas Kinerjanya dalam hal menyelesaikan pembangunan infrastruktur, dalam memulai kegiatan tidak harus tergantung kepada bahan material lengkap baru bisa memulai, dan untuk dukungan dari pemerintah desa sendiri di lapangan agar berjalan dengan baik serta pemanfaatan waktu bekerja dengan maksimal.Sebagai bukti kinerja Pemerintah Desa mengutamakan pelayanan untuk memenuhi kebutuhan dan aspirasi masyarakat yang ada di desa. Responsivitas dan aspirasi akan ditindaklanjuti dalam musrembang desa untuk diusulkan dalam program pembangunan di desa tidak serta merta semua aspirasi bisa masuk kedalam program pembangunan infrastruktur karena aspirasi akan dinilai dari segi kebutuhan masyarakat bukan dari keinginan yang kemudian menjadi prioritas pembangunan di desa.Pelayanan kepada masyarakat adalah hal yang utama, dari 310 jumlah keseluruhan surat yang ada maka peneliti menyimpulkan bahwa pelayanan kantor kepala kampung telah sampai dan bisa dirasakan langsung oleh masyarakat. Meskipun demikian perlu peningkatan pelayanan kepada masyarakat agar lebih memaksimalkan peran pelayanan publik yang baik.